Аржааны Тувы в контексте развития туристско-рекреационных зон - Маадыр, Мая Салчаковна (Новые исследования Тувы, 2013)
Article underlines the main problems in supporting the touristic interest in therapeutic recreation at curative springs of Tuva – the arzhaans.